Image acquisition and processing for multi-channel spectral imaging - Zárate Cáceres, Mario Eduardo (2016)
Nowadays spectrometers are useful in many applications such as bio-medical technology among other industrial fields. State of the art low-cost spectrometers are usually equipped with linear photoelectric array detectors (line detectors). This thesis covers part of the software development for a low-cost multichannel spectrometer using a matrix detector instead of a linear array detector. The image acquisition including an automatic integration time optimizer was implemented. Furthermore, algorithms for data extraction and calibration were developed. Finally, the multi-channel-system with the new software was compared with a high-resolution spectrometer and the results were discussed.